Hubungan antara Social Support dengan Self Efficacy pada Orang dengan HIV/AIDS (ODHA) di Yayasan Kotex Mandiri, Jakarta Timur - Hillalia Nurseha, (2021)
People living with HIV/AIDS or known as PLWHA are discriminated against and stigmatized in society regarding their illness. One of the factors that causes this is the lack of social support provided to PLWHA. Social support can effect an individual's self-efficacy. Social support is information or feedback from others that shows that someone is loved and cared for, valued and respected, and inloved in communication networks. Self-efficacy in an individual's belief or confidence about his abilities. This study aims to determine the relationship between social support and self-efficacy in people living with HIV/AIDS (PLWHA) at the Kotex Mandiri Foundation, East Jakarta. The study used the chi square test with a cross sectional analytic approach, the sample amounted 76 respondents and the sample was taken using probability total sampling technique. The results of the study obtained a p-value of 0.000 which means that there is a positive relationship between social support and self-efficacy in people with HIV/AIDS (PLWHA) at the Kotex Mandiri Foundation, East Jakarta. Researchers suggest PLWHA to be more able to control self-efficacy in daily life as an effort to maintain their immune system, and stay active in relationship with other people in order to further increase social support.